Comparing the Postoperative Complications, Hospitalization Days and Treatment Expenses Depending on the Administration of Postoperative Prophylactic Antibiotics to Hysterectomy - Mi Young Jung; Kyung Yeon Park (Korean Society of Women Health Nursing, 2017)
PURPOSE: This study was conducted to compare postoperative complications, hospitalization days and treatment expenses to postoperative prophylactic antibiotics administrated to hysterectomy or not. METHODS: A retrospective survey study was performed with 128 cases in which elective hysterectomy had undergone. They were divided into two groups by identifying whether postoperative prophylactic antibiotics was administered for hysterectomy: a) one group who received postoperative prophylactic antibiotics and; b) those who did not. Data were collected using the electric medical record at a hospital and analyzed by SPSS 23.0 for χ2 test, t-test and ANCOVA. RESULTS: Postoperative complications including wound infection (p=1.000), pneumonia (p=.496), hematoma (p=.530), and pneumoperitoneum (p=.496) showed no significant differences between two groups. Hospitalization days for the prophylactic antibioticsadministrated group were significantly longer than the non-administered for prophylactic antibiotics (p=.004). The treatment expenses of the prophylactic antibiotics-administrated group were significantly higher than those of the non-administered prophylactic antibiotics (F=4.31, p=.040). CONCLUSION: These results can be provided for the evidence of administrating postoperative prophylactic antibiotics to hysterectomy. Additionally, it can contribute to decreasing the medication errors caused by infrequently administrating postoperative prophylactic antibiotics as well as to lessening likelihood of infection of intravenous injection site.